Association of impulsivity with quality of life and well‐being after alcohol withdrawal treatment. Issue 7 (19th January 2022) - Reichl, Daniela; Enewoldsen, Niklas; Weisel, Kiona K.; Fuhrmann, Lukas; Lang, Catharina; Saur, Sebastian; Berking, Matthias; Zink, Mathias; Ahnert, Andreas; Falkai, Peter; Kraus, Thomas; Hillemacher, Thomas; et al.
Abstract: Objectives: Impulsivity is related to a higher risk of relapse in alcohol use disorders. However, besides drinking behavior, other recovery outcomes like physical and mental health‐related quality of life are at least as important. The present study aimed to fill a research gap regarding the association of different impulsivity facets with health‐related quality of life and well‐being in alcohol use disorder. Methods: Individuals with a primary alcohol use disorder diagnosis ( n  = 167) were interviewed with standardized self‐report measures at the progressed stage of their withdrawal treatment and 6 weeks thereafter. Multiple regression models were calculated to examine the association of impulsivity, craving, and drinking patterns with health‐related quality of life and well‐being 6 weeks after withdrawal treatment, as well as the predictive role of impulsivity assessed during withdrawal for these two outcomes. Results: Craving was associated with health‐related quality of life and well‐being 6 weeks after withdrawal. Likewise, non‐planning and attentional impulsivity were associated with well‐being 6 weeks after withdrawal. Motor impulsivity during withdrawal treatment predicted health‐related quality of life 6 weeks thereafter. Conclusion: Impulsivity seems to be negatively related to health‐related quality of life and well‐being in the first weeks after alcohol withdrawal treatment, probably to a higher extent than drinking patterns, but differentiating between its facets seems to be important. These findings emphasize the importance of treatment approaches aiming at reduced impulsivity in the early recovery process.